2021
DOI: 10.1007/s10620-021-07308-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Subtilis Promotes the Release of 5-HT to Regulate Intestinal Peristalsis in STC Mice via Bile Acid and Its Receptor TGR5 Pathway

Abstract: Background Slow transit constipation (STC) is caused by intestinal peristalsis dysfunction and is closely associated with disturbance of the intestinal microecological balance. Bacillus subtilis plays a positive role in the treatment of STC, but its mechanism needs to be further explored. Aims The purpose of the present study was to explore the effects and mechanism of B. subtilis on the pathophysiology of STC. Methods A STC mouse model was established with compound diphenoxylate, following which B. subtilis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Bacillus coagulans was effective in alleviating the adverse effects of loperamide-induced constipation in Kunming mice [ 36 ]. B. subtilis alleviated the constipation induced by difenoxylate in STC mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus coagulans was effective in alleviating the adverse effects of loperamide-induced constipation in Kunming mice [ 36 ]. B. subtilis alleviated the constipation induced by difenoxylate in STC mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 5-HT can activate the peristaltic reflex by activating 5-HT receptors at the mucosal end of intrinsic primary afferent neurons [ 52 , 53 ]. Previous studies have shown that B. subtilis could promote the release of 5-HT via bile acid and its receptor TGR5 pathway to regulate gastrointestinal motility in STC mice [ 37 ]. Bifidobacterium and Lactobacillus can promote 5-HT secretion from ECCs in constipated mice [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Species contained in SCD probiotics are known to have a positive effect on behavior. For example, Bacillus subtilis, one of the most well-known probiotic bacteria, produces ltryptophan, and the increase in serotonin in the hypothalamus acts as an antidepressant that reduces anxious behavior [24]. In addition, numerous animal studies indicate that Bifidobacterium longum can significantly reduce anxious behavior [25].…”
Section: Resultsmentioning
confidence: 99%
“…The intestinal epithelium's primary food source is short-chain fatty acids (SCFAs), produced by bacterial fermentation of complex carbohydrates in the gut. [32][33][34] IF enhances the production of these SCFAs, whereas Aging is frequently correlated with escalated lipid peroxidation, culminating in oxidative damage. 14,36 This heightened oxidative stress is implicated in intensifying inflammation and fostering protein modifications, subsequently leading to the generation of reactive oxygen species and promoting lymphatic infiltration, a phenomenon that aligns with our observed results.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate that both IF and SCD Probiotics can alleviate these adverse changes associated with aging, indicating their potential as therapeutic strategies. The intestinal epithelium's primary food source is short‐chain fatty acids (SCFAs), produced by bacterial fermentation of complex carbohydrates in the gut 32–34 . IF enhances the production of these SCFAs, whereas SCD Probiotics, through constituents like Bifidobacterium bifidum and Bacillus subtilis , can increase their concentration by regulating other gut bacteria.…”
Section: Discussionmentioning
confidence: 99%